Isolated Extraocular Muscle Infiltration With Plasmacytoma Treated With Localized Injection of Dexamethasone. Issue 2 (June 2015) - Painter, Sally L.; Dickens, Emmy; Elston, John S.
<x xml:space="preserve">Abstract</x> Abstract: Plasmacytoma of the orbit secondary to multiple myeloma is rare and has not previously been reported limited to an extraocular muscle. Conventional treatment is either localized radiotherapy or systemic chemotherapy. We report a case of plasmacytoma within the medial rectus muscle, which regressed completely with localized infiltration of dexamethasone.